Nucleon Generalized Parton Distributions and HolographicModels; Few-Body Systems; Vol. 52, iss. 3-4 - Vega A. Alfredo; Schmidt I. Ivan.; Gutsche T. Thomas; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2012, 2012)
Title screen